Where Is God When It Hurts - Yancey, Philip (Grand Rapids Zondervan Publishing House, 1997)
The author draws from his personal experiences, as well as examples from the Bible to explore the question of why God allows people to suffer pain, and discusses how to respond to one's own pain, as well as the suffering of others.
Keywords: Suffering -- Religious aspects -- Christianity